2016
DOI: 10.1161/strokeaha.115.010402
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the Left Precentral Gyrus Is Associated With Apraxia of Speech in Acute Stroke

Abstract: Background and Purpose-Apraxia of speech (AOS) is a motor speech disorder, which is clinically characterized by the combination of phonemic segmental changes and articulatory distortions. AOS has been believed to arise from impairment in motor speech planning/programming and differentiated from both aphasia and dysarthria. The brain regions associated with AOS are still a matter of debate. The aim of this study was to address this issue in a large number of consecutive acute ischemic stroke patients. Methods-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 34 publications
10
42
2
Order By: Relevance
“…We read with great interest the article by Itabashi et al 1 recently published in Stroke. Using voxel-based lesion-symptom mapping analysis on magnetic resonance imagings of a large number of patients, the authors clearly demonstrated that a restricted area in the left motor cortex is associated with the presentation of apraxia of speech, notably even with that without aphasia.…”
Section: To the Editormentioning
confidence: 98%
See 1 more Smart Citation
“…We read with great interest the article by Itabashi et al 1 recently published in Stroke. Using voxel-based lesion-symptom mapping analysis on magnetic resonance imagings of a large number of patients, the authors clearly demonstrated that a restricted area in the left motor cortex is associated with the presentation of apraxia of speech, notably even with that without aphasia.…”
Section: To the Editormentioning
confidence: 98%
“…Together, it is plausible that this motor area plays an important role in motor speech production. 1 Located in the posterior aspect of the motor cortex, the region may reside in primary motor area (area 4) directly related to motor output, more precisely in the face motor representation (face-M1), rather than in lower motor areas usually implicated in tongue and pharyngeal movements. Indeed, in many of the reports, facial palsy accompanies the impairment in speech motor production.…”
Section: To the Editormentioning
confidence: 99%
“…Meanwhile, involvement of inferior prefrontal gyrus, which plays an important role in semantic processing [1314], and premotor cortex, which is associated with apraxia of speech, may not determine the prognosis of aphasia, but impedes recovery of aphasia [15]. Also, Broca's area is not only associated with poor prognosis, but also with rate or recovery of aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…In several patients, this has been associated with marked asymmetry in subcortical perfusion, especially in the left basal ganglia and thalamus, which the authors in one report concluded may be due to an inflammatory basal ganglia dysfunction interrupting basal ganglia-thalamo-cortical connections, including those to the insula [9]. AOS is associated with damage to the left postcentral gyrus in stroke patients, although imaging excluded this diagnosis [10].…”
Section: Discussionmentioning
confidence: 99%